Packaging Label Reading Behavior as a Reflection of Science Literacy in Elementary School - Putri Chaerunnisa Kartika; Slamet Subiantoro; Kartika Chrysti Suryandari (Journal of Educational Sciences, 2026)
This study aims to describe elementary school students’ behavior in reading food and beverage packaging labels and to reflect this behavior as a form of scientific literacy. The background of this research is the low awareness of students in understanding scientific information presented in daily life, particularly on product packaging. This research employed a descriptive qualitative approach conducted at SDN Serengan 1 Surakarta through observation and interviews with sixth-grade students. The results revealed that students’ habits of reading packaging labels are still low, both at school and at home. Most students tend to focus only on price, taste, and visual appearance without paying attention to nutritional content, food additives, or expiration dates. This condition indicates limited scientific literacy, lack of contextual learning from teachers, and minimal parental guidance. Reading packaging labels is an important aspect of scientific literacy as it trains students to think critically, interpret information, and make evidence-based decisions. Therefore, collaboration between schools, families, and communities is necessary to develop students’ awareness and habits in reading packaging labels from an early age.